1999
DOI: 10.4269/ajtmh.1999.61.350
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of rickettsial spotted fever and ehrlichial infections in a subtropical territory of Jujuy, Argentina.

Abstract: Abstract. Between November 1993 and March 1994, a cluster 6 pediatric patients with acute febrile illnesses associated with rashes was identified in Jujuy Province, Argentina. Immunohistochemical staining of tissues confirmed spotted fever group rickettsial infection in a patient with fatal disease, and testing of serum of a patient convalescing from the illness by using an indirect immunofluorescence assay (IFA) demonstrated antibodies reactive with spotted fever group rickettsiae. A serosurvey was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
29

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 13 publications
2
73
0
29
Order By: Relevance
“…The rate found here sounds high but was similar to the rate found among 726 febrile patients without acute rickettsial infection from the city of Juiz de Fora (Costa 2004), and also to others reported elsewhere (Paddock & Childs 2003). In one of the few serologic surveys in South America, Ripoll et al (1999) found 14% of positivity in Argentina but rates have ranged from 2 to 20% throughout the world (Paddock & Childs 2003). Ehrlichia species particularly E. canis have been recently isolated from Brazilian dogs (Machado 2004) indicating the presence of bacteria belonging to this genus in Brazil.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The rate found here sounds high but was similar to the rate found among 726 febrile patients without acute rickettsial infection from the city of Juiz de Fora (Costa 2004), and also to others reported elsewhere (Paddock & Childs 2003). In one of the few serologic surveys in South America, Ripoll et al (1999) found 14% of positivity in Argentina but rates have ranged from 2 to 20% throughout the world (Paddock & Childs 2003). Ehrlichia species particularly E. canis have been recently isolated from Brazilian dogs (Machado 2004) indicating the presence of bacteria belonging to this genus in Brazil.…”
Section: Discussionmentioning
confidence: 49%
“…The used method for antibody testing in this study (IFA) has the same limitations of other serologic methods added to the subjectivity of the viewer but even though it has been considered the standard for serosurveys of rickettsial infections (Anstey et al 1997, Ripoll et al 1999. The concomitant testing with another method, especially Western blotting (Carpenter et al 1999, Unver et al 2001 could overcome some consequent pitfalls of studies like this but from the practical standpoint the majority of published studies have not been testing more than one method simultaneously (Lemos et al 1994, Galvão 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian spotted fever, which is transmitted by the tick Amblyomma cajennense (12), was initially reported in Brazil more than 60 years ago (14), and cases have increasingly been documented over the last 20 years (10,11,13,43,46). Rickettsiae and rickettsioses have also been recorded in Mexico (52), Costa Rica (19), and Argentina (27,39). The SFG rickettsia agent, R. felis, has been identified in domestic animals and is thought to infect humans in Peru, although these data remain unpublished (C. Moron, unpublished data).…”
mentioning
confidence: 99%
“…El exantema puede ser maculo-papular y a menudo petequial (Figura 1). Suele iniciarse en extremidades con afectación de palmas y plantas y progresar posteriormente al tronco; en ocasiones se presentan equimosis múlti-ples con signos de vasculitis grave (Figura 2) 8,12,16,21,27 . La frecuencia de exantema es variable en las distintas series, habiéndose descrito entre 18 y 100% 8,12,13,20,23,25 .…”
Section: Rickettsia Rickettsiiunclassified